1972
DOI: 10.1530/jrf.0.0280427
|View full text |Cite
|
Sign up to set email alerts
|

Egg Transfer in the Cow: Synchronization Requirements

Abstract: Eggs were transferred surgically from fifty-three donor heifers to ninety-nine recipients which were allocated to different groups according to the degree of synchronization of oestrus between donor and recipient.The pregnancy rate obtained was 0%, 30%, 52\m=.\2%,91\m=.\1%,56\m=.\5%, 40% and 20% where the degree of synchronization of the recipient in relation to the donor was \m=-\3,\m=-\2, \m=-\ 1, 0, + 1, +2, +3 days, respectively. Storage of eggs for periods of up to 6 hr did not influence the pregnancy rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

1974
1974
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 7 publications
2
33
1
1
Order By: Relevance
“…Rowson et al (1971) suggested that competition between embryos within a single uterine horn seemed to occur after unilateral transfer of two embryos. Rowson et al (1972) (Rowson et ai, 1971;Sreenan et al, 1975Sreenan et al, , 1978Anderson et al, 1978) and with that reported after unilateral transfer of two embryos (Boland et ai, 1975;Testart et ai, 1975 (Rowson et al, 1969;Hasler et al, 1987 (Shea, 1981;Lindner & Wright, 1983;King et al, 1985;Hasler et al, 1987). The transfer of embryos produced in vitro evaluated as morphologically excellent, good or fair, resulted in a higher pregnancy rate than the transfer of poor embryos ( Table 2).…”
Section: Pregnancy Diagnosismentioning
confidence: 78%
“…Rowson et al (1971) suggested that competition between embryos within a single uterine horn seemed to occur after unilateral transfer of two embryos. Rowson et al (1972) (Rowson et ai, 1971;Sreenan et al, 1975Sreenan et al, , 1978Anderson et al, 1978) and with that reported after unilateral transfer of two embryos (Boland et ai, 1975;Testart et ai, 1975 (Rowson et al, 1969;Hasler et al, 1987 (Shea, 1981;Lindner & Wright, 1983;King et al, 1985;Hasler et al, 1987). The transfer of embryos produced in vitro evaluated as morphologically excellent, good or fair, resulted in a higher pregnancy rate than the transfer of poor embryos ( Table 2).…”
Section: Pregnancy Diagnosismentioning
confidence: 78%
“…Degrees of asynchrony for successful transfers in other livestock are -3 to +2 days in sheep (Rowson & Moor, 1966b), -2 to +1 days in swine (Webel, Peters & Anderson, 1970) and -2 to +3 days in cattle (Rowson, Lawson, Moor & Baker, 1972 …”
Section: Sixteenmentioning
confidence: 99%
“…Unlike pigs or ewes, transuterine migration of ova or embryos rarely occurs in cattle [27]. It has been postulated that the consequent overcrowding of two embryos within one uterine horn results in the death of one of the embryos in a high proportion of cases [28], even if embryos transferred to the uterine horn ipsilateral to the CL in cows have an increased chance of survival compared to embryos transferred to the contralateral horn [29][30][31]. Also, from the point of view of performing an accurate diagnosis of twin pregnancy, it may be that twin pregnancy established by bilateral transfer will be more diagnosticable than that by unilateral transfer [5].…”
Section: Discussionmentioning
confidence: 99%